Probing astrocyte metabolism in vivo: proton magnetic resonance spectroscopy in the injured and aging brain - Harris, Janna L.; Choi, In-Young; Brooks, William M. (Frontiers in Aging Neuroscience, 2015)
Following a brain injury, the mobilization of reactive astrocytes is part of a complex neuroinflammatory response that may have both harmful and beneficial effects. There is also evidence that astrocytes progressively accumulate in the normal aging brain, increasing in both number and size. These astrocyte changes in normal brain aging may, in the event of an injury, contribute to the exacerbated injury response and poorer outcomes observed in older traumatic brain injury survivors. Here we present our view that proton magnetic resonance spectroscopy (1H-MRS), a neuroimaging approach that probes brain metabolism within a defined region of interest, is a promising technique that may provide insight into astrocyte metabolic changes in the injured and aging brain in vivo. Although 1H-MRS does not specifically differentiate between cell types, it quantifies certain metabolites that are highly enriched in astrocytes (e.g. myo-inositol), or that are involved in metabolic shuttling between astrocytes and neurons (e.g. glutamate and glutamine). Here we focus on metabolites detectable by 1H-MRS that may serve as markers of astrocyte metabolic status. We review the physiological roles of these metabolites, discuss recent 1H-MRS findings in the injured and aging brain, and describe how an astrocyte metabolite profile approach might be useful in clinical medicine and clinical trials.